SiO2@MnOx@Na2WO4@SiO2 core-shell-derived catalyst for oxidative coupling of methane - Park, La-Hee; Jo, Ye Rim; Choi, Jae-Wook; Suh, Dong Jin; Song, Kwang Ho; Ha, Jeong-Myeong (ROYAL SOC CHEMISTRY, 2020)
SiO2@MnOx@Na2WO4@SiO2 core-shell catalysts were prepared and their fabrication was confirmed using transmission electron microscopy. The formation of Mn-based nanosheets on the silica spheres is important for the deposition of nanoscopic Na2WO4. The SiO2@MnOx@Na2WO4@SiO2 core-shell catalysts were used for the oxidative coupling of methane at a temperature of 700-800 degrees C at which the nanostructures were completely destroyed. Although the core-shell structures did not survive the high-temperature oxidative coupling of methane, the selective production of olefins and paraffins can be attributed to highly dispersed Na2WO4 derived from confined core-shell structures.
Keywords: POLYURETHANE FOAM; ETHYLENE; MICROSPHERES; OIL